China's Exchange Rate Trap: Japan Redux? - Mckinnon, Ronald (American Economic Review, 2006)
Today’s American mercantile pressure on China to appreciate the renminbi against the dollar is eerily similar to the American pressure on Japan to appreciate the yen that began over 30 years ago. Indeed, the yen went all the way from 360 to the dollar in August 1971, at the end of the Bretton Woods period of fixed exchange rate parities, to touch 80 to the dollar in April 1995. Then the American government relented and announced a strong dollar policy that signaled the end of “Japan bashing”. But the overvalued yen, and the expectation of appreciation, destabilized the Japanese financial system; the bubble economy of the late 1980s was followed by a deflationary slump and a zero-interest liquidity trap in the 1990s [McKinnon and Ohno 1997]. At least some of today’s critics of East Asian countries ’ pegging to the dollar would agree that international saving imbalances rather than misaligned exchange rates are the root cause of the U.S. current-account deficit. One can argue whether it is mainly a saving deficiency in the United States or a saving glut in the rest of the world [Bernanke 2005]. Either way, the central position of the United States under the world dollar standard gives it alone an unlimited international line of credit in its own currency. However, suppose that the U.S. trade deficit is misdiagnosed to result from a misaligned exchange rate, so that a surplus country on the dollar’s periphery is forced to appreciate against the world’s dominant money. It will suffer a slowdown in economic